Breast cancer detection across dense and non-dense breasts: Markers of diagnostic confidence and efficacy. (1st January 2022) - Hadadi, Ibrahim; Rae, William; Clarke, Jillian; McEntee, Mark; Ekpo, Ernest
Background: The impact of radiologists' characteristics has become a major focus of recent research. However, the markers of diagnostic efficacy and confidence in dense and non-dense breasts are poorly understood. Purpose: This study aims to assess the relationship between radiologists' characteristics and diagnostic performance across dense and non-dense breasts. Materials and methods: Radiologists specialising in breast imaging ( n = 128) who had 0.5–40 (13±10.6) years of experience reading mammograms were recruited. Participants independently interpreted a test set containing 60 digital mammograms (40 normal and 20 abnormal) with similarly distributed breast densities. Diagnostic performance measures were analysed via Jamovi software (version 1.6.22). Results: In dense breasts, breast-imaging fellowship completion significantly improved specificity ( p = 0.004), location sensitivity ( p = 0.01) and the area under the curve (AUC) of the receiver operating characteristic ( p = 0.03). Only participation in BreastScreen reading significantly improved all performance metrics: specificity ( p = 0.04), sensitivity ( p = 0.005), location sensitivity ( p < 0.001) and AUC ( p < 0.001). Reading > 100 mammograms weekly significantly improved sensitivity ( p = 0.03), location sensitivity ( p = 0.001), and AUC ( p = 0.03).In non-dense breasts, breast fellowship completion significantly improved sensitivity ( p = 0.02), location sensitivity ( p = 0.04) and AUC ( p = 0.002). Participation in BreastScreen reading and reading > 100 mammograms weekly significantly improved only sensitivity ( p = 0.002 and p = 0.003, respectively) and location sensitivity ( p < 0.001 and p < 0.001, respectively). Conclusion: Participating in screening programs, breast fellowships and reading > 100 mammograms weekly are important indicators of the diagnostic performance of radiologists across dense and non-dense breasts. In dense breasts, optimal performance resulted from participation in a breast screening program.